Acquired cervical scoliosis in two dogs with inflammatory central nervous system disease. (27th August 2021) - Poad, Lydia; De Decker, Steven; Fenn, Joe
Abstract: Acquired cervical scoliosis previously has been reported in dogs as a clinical sign associated with Chiari‐like malformation and syringomyelia but has not been described with inflammatory central nervous system disease. A 9‐month‐old Flat‐Coated Retriever was presented with an acute onset of cervical scoliosis with no other neurological deficits. Magnetic resonance imaging identified a focal, poorly defined intramedullary lesion within the cranial cervical spinal cord. Cerebrospinal fluid (CSF) analysis indicated mononuclear pleocytosis consistent with a diagnosis of meningomyelitis of unknown etiology. A second dog, a 3‐year‐old female spayed German Shepherd, developed an acute onset of cervical scoliosis with mild generalized proprioceptive ataxia 2 months after commencing immunosuppressive corticosteroid treatment for presumed steroid‐responsive meningitis‐arteritis. Magnetic resonance imaging at the time of diagnosis disclosed a similar intramedullary lesion within the cranial cervical spinal cord, with a neutrophilic pleocytosis on CSF analysis. Both dogs were treated with immunosuppressive dosages of prednisolone, along with cytosine arabinoside in the first dog, with resolution of cervical scoliosis seen in both. To our knowledge, this is the first report of acute onset acquired, reversible cervical scoliosis in dogs with presumed immune‐mediated meningomyelitis.